Comparison of mechanisms for the direct, gas phase, partial oxidation of methane to methanol. (21st September 2021) - Turan, Evren M.; van Steen, Eric; Möller, Klaus P.
Highlights: A wide range of reported, experimental data were used to compare mechanisms. All the mechanisms are found to be inaccurate. The most plausible mechanism has a selectivity error of 17%. Abstract: Numerous mechanisms have been proposed for the direct, homogeneous, partial oxidation of methane to methanol system. No thorough comparison of them to experimental data, and to each other, has been reported. In this work six mechanisms are tested against over 200 operating points from published literature. All the examined mechanisms are found to be inaccurate, with the most accurate mechanism, M Vedeneev, C 1 (Arutyunov et al., 1996), having an average selectivity error of 17%. In addition, it was found that some mechanisms showed behaviour that was not observed in the literature and were deemed unsuitable for the reaction system. As such all of the available mechanisms do not adequately describe the gas phase methane to methanol system.